Effect of Growth Regulators on Germination and Early Seedling Growth of Salt Stressed Sensitive and Tolerant Genotypes of Rice - Panda, D.; Ghosh, D. C. (International Journal of Bio-resource and Stress Management, 2018)
The effect of growth regulators like Ascophyllum nodosum extract (0.1%), Triacontanol (5 ppm) and 28-Homobrassinolide (1ppm) in ameliorating salt stress in two genotypes of rice (IR-29 and CSR-4) under three salinity levels viz. S0=Non saline as control, S1=40 mmol l-1 NaCl+20 mmol l-1 Na2SO4+20 mmol l-1 CaCl2 (ECe 9.6 dSm-1) and S2=60 mmol l-1 NaCl+30 mmol l-1 Na2SO4+30 mmol l-1 CaCl2 (ECe 13.5 dSm-1) was studied on germination, seedling growth, physiological and biochemical parameters. The presowing treatment of Ascophyllum nodosum 0.1% extract and 28-Homobrassinolide 1 ppm were found to be beneficial in inducing salt tolerance in both sensitive (IR-29) and tolerant genotype (CSR-4). These growth regulators significantly increased the germination, seedling vigour and membrane stability index in rice seedlings under saline condition as compared to control (water soaked). Boththegrowth regulators significantly increased the activity ofantioxidant enzymeslike super oxide dismutase, glutathione reductase, catalase and peroxidase under salt stress condition as compared to that of Triacontanol 5 ppm and water soaked seeds.